(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Easterine Kire’s Sky is My Father: A Naga Village Remembered intricately portrays the life, belief systems, and cultural practices of the Nagas, focusing on Khonoma village. The novel highlights the centrality of taboos, rituals, and oral traditions in shaping the Naga worldview. Rituals—ranging from funerals, childbirth, marriage, tiger hunting, and chicken sacrifices to Genna days and Terhase ceremonies—reveal the intricate interplay between spiritual, social, and communal life. This paper examines how Kire presents these practices, demonstrating that Naga religion and spirituality are embedded in everyday life, agriculture, and communal survival. It also explores patriarchal restrictions, showing how gender roles influence ritual participation. The study highlights the resilience of indigenous spirituality amidst colonial incursions and modern pressures, emphasizing how Naga faith sustains cultural identity and continuity.